Empowering Virtuous Citizenship: A Curriculum-Driven Initiative for Community Good Character by Madrasah Aliyah Teachers - Mariatul Hikmah (STAI Hubbulwathan Duri, 2024)
Madrasah Aliyah has shifted from traditional competitive academic models to an independent curriculum that emphasizes holistic development and cooperation. This qualitative study, involving interviews, observations, and document analysis, assessed the curriculum's implementation and impact, involving stakeholders like educators, the madrasa head, and ministry officials. The findings indicate that the curriculum substantially supports individual growth, ethical character development, and community involvement. The madrasa head plays a pivotal role by integrating character values into daily practices, fostering an ethical and respectful community. Educators actively participate in developing and executing the curriculum, tailored to meet diverse student needs. This curriculum enhances essential life skills—respect, honesty, and justice—through practical applications, aligning with broader educational objectives of preparing well-rounded individuals for societal challenges. However, the study’s limitation to one institution may affect the generalizability of the findings. Future research should expand to multiple institutions to verify these outcomes and explore the curriculum's broader applicability. Madrasah Aliyah Nurulfalah Airmolek’s innovative approach provides a model for other schools to incorporate character education into their frameworks, underscoring the importance of leadership in fostering significant educational and social transformations.